"Jan Kasprowicz. W siedemdziesięciolecie śmierci. Materiały Międzynarodowej Sesji Naukowej, Olsztyn 17-19 X 1996", pod red. Jana Kaczyńskiego, Olsztyn 1999 - Zienkiewicz, Tadeusz (Acta Polono-Ruthenica, 2000)
—-